Theoretical Investigations of the Oxygen Reduction Reaction on Pt(111) - Keith, John A.; Jerkiewicz, Gregory; Jacob, Timo (Chemphyschem, 2010)
Computational modeling can provide important insights into chemical reactions in both applied and fundamental fields of research. One of the most critical processes needed in practical renewable energy sources is the oxygen reduction reaction (ORR). Besides being the key process in combustion and corrosion, the ORR has an elusive mechanism that may proceed in a number of complicated reaction steps in electrochemical fuel cells. Indeed, the mechanism of the ORR on highly studied Pt(111) electrodes has been the subject of interest and debate for decades. Herein, we first outline the theory behind these types of simulations and then show how to use these quantum mechanical approaches and approximations to create a realistic model. After reviewing the performance of these methods in studying the binding of molecular oxygen to Pt(111), we then outline our own results in elucidating the ORR and its dependence on environmental parameters, such as solvent, thermodynamic energies, and the presence of an external electrode potential. This approach can, in principle, be applied to other equally complicated investigations of other surfaces or electrochemical reactions. Modeling an elusive system: A current review on the mechanism of the oxygen reduction reaction (ORR) on Pt(111) (see figure) is presented. Beginning with an abridged introduction to fundamental computational chemistry methods, the authors investigate the multiple‐pathway ORR and the influences of solvation, thermal energy (e.g. entropy), and electrode potential on each step.